THE TAI CHI ROLES IN REDUCING FATIGUE, PAIN, AND TNF-a PLASMA LEVEL ON BREAST CANCER PATIENTS: A SYSTEMATIC REVIEW - Putri Yekti Budi Asih; I Putu Edra Putra Indrawan; Andhika Putri Perdana; Putu Ratna Candra Puspita; Vera Pravitasari Susila; Nila Wahyuni; I Putu Gede Adiatmika (Sport and Fitness Journal, 2022)
Background: Tai Chi and many other Mind-body therapies have been very popular over the last few decades as useful tools for reducing stress and improving health. These methods are non-invasive and inexpensive. There are several reports showing that Tai Chi (TC) can regulate the host's immune system in many illnesses. This review summarizes the Tai Chi’s influence on breast cancer (BC) patients. Survivors of breast cancer often experience symptoms that reduce their quality of life during and after treatment, such as cognitive dysfunction, fatigue, sleep disturbances, depression, pain, and weight gain. The proinflammatory biomarkers like TNF-a, IL-1, IL-6 which activated through the central nervous system were believed inducing fatigue, pain , and other complications that caused hidarance on life activity. This becomes a serious problem as the number of survivors increases. The results of most studies show that Tai Chi reduced fatigue, pain, plasma levels of TNF-a and overall quality of life in breast cancer patients. Objective: To identify and evaluate the effect of TC training on inflammatory biomarkers, especially TNF-a, pain, and cancer-related fatigue (CRF) in breast cancer patients. Methods: Journal searching processes were performed through five electronic databases (ProQuest, Sciencedirect, PubMed, Google Scholar, and Sage Publications) and restricted from 2012 to 2022. The search strategy on the electronic databases was using terms like 'tai ji', 'tai chi', 'tumor necrosis factor-alpha', 'Interleukin-6', 'fatigue', 'pain', 'breast cancer', ‘biomarker’, 'TNF', 'TNF-a', and 'TNF-alpha'. The limitation of the study was only using academic journals and limited to Tai Chi training as an intervention. Reviewers obtained as many as 1.557 research journals. Then the reviewers analyzed the journal's contents obtained based on the eligibility of the topics, indexes or journal ratings through the Scimagojr website with journal criteria that met Q1 and Q2 quality, sample size, results from each journal, and limitations that occurred. Result: 15 journals were chosen to be reviewed and discussed about the intervention of Tai Chi, research methodology and study results using pain, fatigue and TNF-a biomarker. Conclusion: Tai Chi seems to be effective to reduce pain, cancer-related fatigue, and improves quality of life for breast cancer patients. accepts to TNF-a level plasma seems to be no different between usual care dan Tai chi practice. Moreover, it requires rigorous methodologies and randomized controlled trials to provide more reliable evidence.